Spectroscopic studies of oils and its synthesized bio-polymer - Sulong, Nurulsaidatulsyida; Mohd Rus, Anika Zafiah; Mat Hassan, Nik Normunira; Marsi, Noraini (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), 2018)
Nowadays, the development of alternatives to petroleum based - natural based polymeric materials were grow rapidly due to contemporary challenge attributable to environmental concerns and the effects of fluctuating oil prices.Triglycerides, the primary components of vegetable oils, are an abundant, renewable, and widely investigated as the alternative feedstock for polymeric materials [1], In this study, 3 types of cooking oil was used such as, Virgin Oil (VO), ‘Popia’ Oil (PO), and Mixed Oil (MO) for the synthesis of bio-monomer named as Virgin Oil Monomer (VOM), Popia Oil Monomer (POM) and Mixed Oil Monomer (MOM). These bio-monomers then converted to the bio-polymers named as Virgin Oil Polymer (VOP), Popia Oil Polymer (POP) and Mixed Oil Polymer (MOP). The spectroscopic properties of oils, bio-monomers and bio-polymers were tested using Fourier Transform Infrared Spectroscopy (FTIR). The characteristic peak 3010.65 cm-1 was attributed to the C–H stretching of VO, PO, and MO. The peaks at 3010.65 cm-1 disappear during the epoxidation process and new peak appear around 3330cm-1 – 3450 cm-1 in the VOM, MOM and POM attributed to the hydroxyl groups (O-H). For VOP, MOP, and POP, a strong 3330 cm-1 - 3345 cm-1 absorption band characteristic of the N–H group and an absorption band characteristic of the C=O group centered around 1700 cm-1 are present in all the FTIR spectra. Hence, its shows all types of oils were successfully converted to the bio-monomers and bio-polymers as refer to the absorption band in spectroscopic analysis.